Membangun Aplikasi Natural Language Processing Menggunakan Instant Messenger Untuk Informasi Bencana (Publikasi Eksternal, 2013)
Instant  messaging  is  a  communication  facility  to the users of internet chat. By using this facility, the   user can communicate  by  sending  a  text  message  to  another  user.  In addition, Instant Messaging also serves to exchange files in a peer to peer. Availability of vast resources and varied, as well as  the  rapid  development  of  techniques  Natural  Language Processing  (NLP),  Information  Extraction  (IE)  and Information Retrieval (IR) greatly influenced the development of  QA  (Question  Answering)  system,  which  used  to  only  be able to answering the questions are limited to a field (domain) specific  to  based  on  structured  information  sources  such  as databases, up to now can answer different types of questions, referring to a collection of information from unstructured text.This  research  is  utilizing  receipts  Instant  Messenger  Google Talk  service  to  provide  information  to  your  questions on the online  disaster.  The  system  works  by  utilizing  a  database  of various sites on the Internet. The research is fitted with a QA application system using disaster information crawler results of some catastrophic news site